PENGARUH PENGGUNAAN APLIKASI YOUTUBE DAN FACEBOOK TERHADAP HASIL BELAJAR MATEMATIKA - Dwi Parinata (Jurnal Ilmiah Mahasiswa Matematika Realistik, 2021)
The purpose of this study was to determine the effect of using YouTube and Facebook applications on mathematics learning outcomes. This research uses quantitative research. The subjects of this study were students of prospective Mathematics Teachers at the Indonesian Technocrat University and UIN Raden Intan Lampung batch 2018 with 20 respondents. This research was conducted in 5 stages namely; 1) Distributing questionnaires in the form of Google Forms, 2) Assessing the results of prospective Mathematics Teacher students at the Indonesian Technocrat University and UIN Raden Intan Lampung batch 2018, 3) Testing the validity and reliability of the instrument, 4) interpreting the results of the questionnaire calculations, 5) looking for the relationship between The Effect of Using YouTube and Facebook Applications on Mathematics Learning Outcomes. The Questionnaire of the Effect of Using YouTube and Facebook Applications on Mathematics Learning Outcomes obtained a High qualification with the results of reliability calculations using Cronbach Alpha of 0.838. And from the results of the calculations in table 5, the correlation value is -0.074, it can be said that based on the guidelines for the degree of relationship calculation, the correlation between two variables is declared "no correlation". In conclusion, there is no significant relationship between the effect of using YouTube and Facebook applications on mathematics learning outcomes for prospective mathematics teachers at the Indonesian Technocrat University and UIN Raden Intan Lampung batch 2018. Keywords: Learning Mathematics, Facebook, Mathematics, Application Use, YouTube.